THE POSITION OF IMAM AL-BUKHARI’S “SAHIH” AMONG HADITH COLLECTIONS - Doniyor Makhamatvalievich Murodov (International Journal of Literature and Language Studies, 2026)
This article analyzes Imam Bukhari’s “al-Sahih” from the point of view of Source Studies, compares it with other books on the Science of hadith, and explains its methods. In addition, the article also highlights other books which were written using “al-Sahih”. It also gives information about the place of “al-Sahih” among other hadith collections.